Digital Savvy as a Catalyst for Digital Transformation in the 5.0 Era: Building an Adaptive Society - Ahmat Hufron; Mulyono; Rani Iswari, Hanif (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2025)
Digital transformation in the 5.0 era has become a necessity for society to adapt to the rapid development of technology. This study aims to explore the role of digital savvy as a catalyst in the digital transformation process. The method used in this study is a systematic literature review (SLR), by analyzing 25 scientific articles obtained through a search on Google Scholar using relevant keywords such as "digital transformation", "Society 5.0", and "digital skills". The article selection process was carried out through several stages, namely identification, screening, eligibility checking, and inclusion. Bibliometric analysis was conducted with the help of the VOSviewer application to map and analyze the relationships between articles and relevant research trends. The results show that the level of digital skills of individuals and society makes a significant contribution to the success of digital transformation, as well as in forming a more adaptive and innovative society. These findings are expected to provide insights for stakeholders in designing human resource development strategies that support digital transformation in the 5.0 era